2012
DOI: 10.1128/mcb.00290-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of SUMOylation in Full Antiestrogenicity

Abstract: The selective estrogen receptor downregulator (SERD) fulvestrant can be used as second-line treatment for patients relapsing after treatment with tamoxifen, a selective estrogen receptor modulator (SERM). Unlike tamoxifen, SERDs are devoid of partial agonist activity. While the full antiestrogenicity of SERDs may result in part from their capacity to downregulate levels of estrogen receptor alpha (ER␣) through proteasome-mediated degradation, SERDs are also fully antiestrogenic in the absence of increased rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(73 citation statements)
references
References 96 publications
9
64
0
Order By: Relevance
“…Proteomics also identified K299 in the hinge region and K472 in the steroid-binding domain to be sumoylated. The selective estrogen receptor downregulator fulvestrant induces rapid and strong sumoylation of ERα at K171, K180, K299, and K472 residue [151]. These results indicate that ERα sumoylation contributes to full antiestrogenicity in the absence of accelerated receptor turnover.…”
Section: Sumoylation Of Estrogen Receptormentioning
confidence: 86%
“…Proteomics also identified K299 in the hinge region and K472 in the steroid-binding domain to be sumoylated. The selective estrogen receptor downregulator fulvestrant induces rapid and strong sumoylation of ERα at K171, K180, K299, and K472 residue [151]. These results indicate that ERα sumoylation contributes to full antiestrogenicity in the absence of accelerated receptor turnover.…”
Section: Sumoylation Of Estrogen Receptormentioning
confidence: 86%
“…2007, Kocanova et al . 2010, Hilmi et al . 2012), decreased steady-state levels of ERα were observed to variable extents in the presence of endoxifen (a tamoxifen metabolite), raloxifene and bazedoxifene.…”
Section: Role Of Post-translational Modifications Of Erα By Ubi-like mentioning
confidence: 99%
“…Further, although the steady-state levels of transfected ERα were not decreased but rather increased in the presence of ICI 182,780 in HepG2 cells, ICI 182,780 still acted as an inverse agonist in these cells, whereas tamoxifen had partial agonist activity (Lupien et al . 2007, Hilmi et al . 2012).…”
Section: Role Of Post-translational Modifications Of Erα By Ubi-like mentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of the F-domain in the antagonist-dependent LBD dimerization occurred not only with the AF-2-mutated ERα but also with WT ERα (28). A portion of the antagonistic effect of ICI on WT ERα results from the stimulation of ERα proteolysis (28)(29)(30), and it was recently reported that ICI induces SUMOylation of human ERα protein and that the mutations of H12 reduced SUMOylation in the presence of ICI (31). These results suggest that the prevention of ICI-dependent proteolysis maintains the dimer formation of AF-2-mutated ERα and that this increases ERE binding and transcription activation.…”
Section: Ici Acts As An Erα Agonist On Trabecular Bone Mass and Uterumentioning
confidence: 99%